Beneficiaries of mergers & acquisitions in South Africa - Ndadza, Tshifhango Emmanuel (My University, 2014)
Anecdotal evidence shows that Africa experienced increasing foreign direct investment inflows for the period 2007-2011 and half of Africa’s top merger and acquisition deals in 2012 targeted firms from South Africa. Therefor the value of merger and acquisition deals in South Africa and Africa as a whole requires more robust and rigorous research like is the case in developed countries. This research adds to the merger and acquisition literature by determining whether these deals create value for the shareholders of the South African involved. The research also assesses the social impact that these M&A deals have on the South African economy, particularly on employment.
Thesis (M.M. (Finance & Investment))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2014.